Solid electrolyte membrane and all-solid-state battery comprising same

Through the solid electrolyte particles of different Yang's modulus and particle size in the solid electrolyte film of the all -solid battery, and adjust the weight ratio, solve the problem of lithium ion migration resistance caused by the high hardness of the solid electrolyte, and achieve a better one. Battery performance.

CN119384747APending Publication Date: 2025-01-28LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480002973.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-05-16
Filing Date
2024-04-12
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In all-solid-state batteries, the high hardness of the solid electrolyte membrane leads to a significant increase in the resistance to lithium ion migration, reducing the performance of the battery.

Method used

By containing the first and second solid electrolyte particles in the solid electrolyte film, and adjust the size, the average particle size and weight ratio of the Yang's model to improve the interface binding force of the positive electrode and the solid electrolyte, the negative electrolyte, and the solid electrolyte film, To reduce the resistance at the interface.

Benefits of technology

By optimizing the composition and structure of the solid electrolyte, the resistance between the positive and negative electrolytes and the solid electrolyte film is significantly reduced, and the life characteristics and magnification characteristics of the full solid battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384747A_ABST
    Figure CN119384747A_ABST
Patent Text Reader

Abstract

The present invention relates to a solid electrolyte membrane for an all-solid-state battery, comprising first solid electrolyte particles and second solid electrolyte particles, in which the first solid electrolyte particles have a higher Young's modulus than the second solid electrolyte particles, and the first solid electrolyte particles and the second solid electrolyte particles have an average particle diameter (D50) of 1 [mu] m to 5 [mu] m, the first solid electrolyte particles and the second solid electrolyte particles are mixed in a weight ratio of 2: 8 to less than 7: 3, and an all-solid-state battery comprising the solid electrolyte membrane.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of and priority to Korean Patent Application No. 10-2023-0063088, filed on May 16, 2023, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] The present invention relates to a solid electrolyte membrane and an all-solid-state battery comprising the solid electrolyte membrane. Background Art

[0004] Various batteries are being researched to overcome the limitations of current lithium secondary batteries in terms of capacity, safety, power output, large-scale and miniaturization.

[0005] For example, research is ongoing in academia and industry on metal-air batteries that have a very large theoretical capacity compared to lithium secondary batteries, all-solid-state batteries that do not have an explosion risk in terms of safety, supercapacitors in terms of power output, NaS batteries or redox flow batteries (RFB) in terms of large-scale development, and thin-film batteries in terms of miniaturization.

[0006] All-solid-state batteries are batteries that use solid electrolytes instead of liquid electrolytes used in conventional lithium secondary batteries, and they do not use flammable solvents, so that fire or explosion caused by the decomposition reaction of conventional electrolytes does not occur at all, thus greatly improving safety. In addition, since lithium (Li) metal or lithium alloy can be used as the negative electrode material, it has the advantage of significantly improving the energy density per unit mass and volume of the battery.

[0007] All-solid-state batteries are manufactured by placing a solid electrolyte membrane between the positive and negative electrodes and then pressing them under high pressure. + ) The smoother the migration at the interface between the positive electrode and the solid electrolyte membrane and the interface between the negative electrode and the solid electrolyte membrane, the better the performance of the all-solid-state battery. However, if the hardness of the solid electrolyte membrane is high, the resistance of lithium ion migration may significantly appear at the interface between the positive electrode and the solid electrolyte membrane and the interface between the negative electrode and the solid electrolyte membrane, which can reduce the performance of the all-solid-state battery.

[0008] Therefore, it is necessary to improve the performance of all-solid-state batteries by minimizing the resistance at the interface between the positive electrode and the solid electrolyte membrane and at the interface between the negative electrode and the solid electrolyte membrane.

[0009] [Prior art literature]

[0010] [Patent Document]

[0011] Korean Patent Publication 10-2021-0087919 Summary of the invention

[0012] [Technical issues]

[0013] The inventors have confirmed that the solid electrolyte membrane comprises first solid electrolyte particles and second solid electrolyte particles, and adjusting the Young's modulus, average particle size and weight ratio of the first solid electrolyte particles and the second solid electrolyte particles can improve the interfacial bonding force between the positive electrode and the solid electrolyte membrane and the interfacial bonding force between the negative electrode and the solid electrolyte membrane, thereby minimizing the resistance generated at the interface, thereby completing the present invention.

[0014] Therefore, an object of the present invention is to provide a solid electrolyte membrane for an all-solid-state battery, in which the solid electrolyte membrane can reduce the resistance appearing at the interface between the positive electrode and the solid electrolyte membrane and at the interface between the negative electrode and the solid electrolyte membrane.

[0015] Furthermore, the present invention aims to provide an all-solid-state battery having excellent life characteristics and rate characteristics by including the solid electrolyte membrane.

[0016] [Technical solution]

[0017] In order to achieve the above object, the present invention provides a solid electrolyte membrane for an all-solid-state battery, comprising: a first solid electrolyte particle and a second solid electrolyte particle,

[0018] The Young's modulus of the first solid electrolyte particle is higher than the Young's modulus of the second solid electrolyte particle.

[0019] The average particle size (D50) of the first solid electrolyte particles and the second solid electrolyte particles is 1 μm to 5 μm.

[0020] The first solid electrolyte particles and the second solid electrolyte particles are mixed in a weight ratio of less than 7:3 to 2:8.

[0021] The present invention also provides an all-solid-state battery, which comprises: a positive electrode, a negative electrode and a solid electrolyte membrane arranged therebetween.

[0022] The solid electrolyte membrane is the solid electrolyte membrane of the present invention.

[0023] [Beneficial Effects]

[0024] The solid electrolyte membrane for an all-solid-state battery of the present invention comprises a first solid electrolyte particle and a second solid electrolyte particle, and by adjusting the Young's modulus, average particle size and weight ratio of the first solid electrolyte particle and the second solid electrolyte particle, it is possible to improve the interfacial bonding force between the positive electrode and the solid electrolyte membrane and the interfacial bonding force between the negative electrode and the solid electrolyte membrane, thereby minimizing the resistance generated at the interface.

[0025] Therefore, an all-solid-state battery including the solid electrolyte membrane of the present invention can have excellent life characteristics and rate characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a life characteristic measurement graph of Example 1, Comparative Example 1 and Comparative Example 2.

[0027] Figure 2 This is a lifetime characteristic measurement graph of Comparative Example 4.

[0028] Figure 3 It is a rate characteristic measurement graph of Example 1, Comparative Example 2 and Comparative Example 3. DETAILED DESCRIPTION

[0029] Hereinafter, the present invention will be described in more detail.

[0030] The terms and words used in this specification and claims should not be interpreted as their ordinary meanings or dictionary meanings, but should be interpreted as meanings and concepts consistent with the technical idea of ​​the present invention based on the principle that the inventor can define the concept of the terms in the way he / she believes is most suitable to describe his / her invention.

[0031] The terms used in the present invention are only used to describe specific examples and are not intended to limit the present invention. Singular expressions include plural meanings unless the context clearly indicates otherwise. In the present invention, the terms "include / comprise" or "have" and the like are intended to indicate the presence of the features, quantities, steps, actions, components, parts or combinations thereof, and are not intended to exclude the presence or addition of more than one other features, quantities, steps, actions, components, parts or combinations thereof.

[0032] Solid electrolyte membrane for all-solid-state batteries

[0033] The present invention relates to a solid electrolyte membrane for an all-solid-state battery, comprising: first solid electrolyte particles and second solid electrolyte particles,

[0034] The Young's modulus of the first solid electrolyte particle is higher than the Young's modulus of the second solid electrolyte particle.

[0035] The average particle size (D50) of the first solid electrolyte particles and the second solid electrolyte particles is 1 μm to 5 μm.

[0036] The first solid electrolyte particles and the second solid electrolyte particles may be mixed in a weight ratio of less than 7:3 to 2:8.

[0037] The solid electrolyte membrane for an all-solid-state battery of the present invention comprises a first solid electrolyte particle and a second solid electrolyte particle. The first solid electrolyte particle and the second solid electrolyte particle have different Young's modulus, and the Young's modulus of the first solid electrolyte particle may be higher than the Young's modulus of the second solid electrolyte particle. By including heterogeneous solid electrolyte particles having different Young's moduli, the Young's modulus of the solid electrolyte membrane can be adjusted. Thus, the resistance generated at the interface between the positive electrode of the all-solid-state battery and the solid electrolyte membrane and at the interface between the negative electrode of the all-solid-state battery and the solid electrolyte membrane can be reduced, and thus an all-solid-state battery with improved life characteristics and rate characteristics can be provided.

[0038] The Young's modulus of the first solid electrolyte particles may be 40 GPa to 80 GPa, preferably 40 GPa to 60 GPa, and most preferably 40 GPa to 50 GPa. Generally, the larger the Young's modulus of the particles, the harder the particles are, and they are less fragile. Since the first solid electrolyte particles have a Young's modulus within the above range, the solid electrolyte membrane can maintain its shape even when a volume change occurs during charging and discharging of the all-solid-state battery.

[0039] In addition, the Young's modulus of the second solid electrolyte particles can be 5GPa to 30GPa, preferably 10GPa to 25GPa, and most preferably 15GPa to 20GPa. Since the second solid electrolyte particles have a Young's modulus within the above range, they can be easily deformed under high pressure, so that the combination of the solid electrolyte membrane and the electrode is excellent. In addition, the second solid electrolyte particles can be located between the first solid electrolyte particles to minimize the pores, which can promote lithium ion migration and play a role in improving the interface bonding between the solid electrolyte membrane and the electrode.

[0040] The difference in Young's modulus between the first solid electrolyte particle and the second solid electrolyte particle may be 15 GPa to 50 GPa, preferably 20 GPa to 40 GPa. When the difference in Young's modulus is less than 15 GPa, the first solid electrolyte particle may have a low Young's modulus, or the second solid electrolyte particle may have a high Young's modulus. If the difference in Young's modulus is less than 15 GPa due to the low Young's modulus of the first solid electrolyte particle, the physical rigidity of the solid electrolyte membrane may be reduced, and if the second solid electrolyte particle has a high Young's modulus, the effect of improving the interface bonding between the solid electrolyte membrane and the electrode cannot be expected. In addition, if the difference in Young's modulus is higher than 40 GPa, the Young's modulus of the first solid electrolyte particle increases, thereby the interfacial bonding force between the solid electrolyte membrane and the electrode may be reduced, resulting in a reduction in interface resistance.

[0041] In addition, the average particle size (D50) of the first solid electrolyte particles and the second solid electrolyte particles is the same as each other, and can be 1 μm to 5 μm, preferably 2 μm to 3 μm. If the average particle size (D50) of the first solid electrolyte particles and the second solid electrolyte particles is less than 1 μm, it is not easy to disperse the first solid electrolyte particles and the second solid electrolyte particles when manufacturing the solid electrolyte membrane, and a solid electrolyte membrane with an uneven surface may be manufactured. As a result, the performance of an all-solid-state battery including the solid electrolyte membrane may be reduced. In addition, since the first solid electrolyte particles and the second solid electrolyte particles have an average particle size within the above range, in the solid electrolyte membrane manufacturing process, it is easy to disperse the first solid electrolyte particles and the second solid electrolyte particles during the slurrying process, so that a solid electrolyte membrane with a uniform surface can be manufactured.

[0042] The first solid electrolyte particles and the second solid electrolyte particles can be mixed in a weight ratio of less than 7:3 to 2:8, preferably in a weight ratio of 6:4 to 4:6, and most preferably in a weight ratio of 5:5. If the content of the first solid electrolyte particles exceeds the above range, the Young's modulus of the solid electrolyte membrane may be too high, resulting in a low interfacial bonding force between the solid electrolyte membrane and the electrode, thereby reducing the life characteristics of the all-solid-state battery containing the solid electrolyte membrane. On the other hand, if the content of the first solid electrolyte particles is lower than the above range, the ionic conductivity of the solid electrolyte membrane may decrease, resulting in an increase in resistance, and the life characteristics and rate characteristics of the all-solid-state battery containing the solid electrolyte membrane may deteriorate.

[0043] In the present invention, the Young's modulus of the solid electrolyte membrane may be 20 GPa to 40 GPa, preferably 25 GPa to 35 GPa. The solid electrolyte membrane of the present invention comprises a first solid electrolyte particle and a second solid electrolyte particle, wherein the Young's modulus of the first solid electrolyte particle is higher than the Young's modulus of the second solid electrolyte particle, the average particle size (D50) of the first solid electrolyte particle and the second solid electrolyte particle is 1 μm to 5 μm, and the first solid electrolyte particle and the second solid electrolyte particle are mixed in a weight ratio of less than 7:3 to 2:8. The second solid electrolyte particle has a low Young's modulus and has a smooth property, and the second solid electrolyte particle is located between the first solid electrolyte particles, so that the space (ie, pores) formed between the first solid electrolyte particles can be minimized, so that the interfacial bonding force between the solid electrolyte membrane and the electrode can be improved, thereby reducing the resistance of lithium ion migration, that is, reducing the interface resistance occurring at the interface between the solid electrolyte membrane and the electrode. Therefore, the life characteristics and rate characteristics of the all-solid-state battery containing the solid electrolyte membrane can be improved.

[0044] Even if a solid electrolyte membrane containing one type of solid electrolyte has the same Young's modulus as that of the present invention, it is impossible to minimize the space formed between the solid electrolyte particles to achieve the effect of reducing the interface resistance.

[0045] The first solid electrolyte particles and the second solid electrolyte particles may be at least one selected from the group consisting of a sulfide-based solid electrolyte, a polymer-based solid electrolyte, and an oxide-based solid electrolyte, and are preferably a sulfide-based solid electrolyte.

[0046] Furthermore, the first solid electrolyte particles and the second solid electrolyte particles may be identical to each other, differing only in Young's modulus.

[0047] The sulfide-based solid electrolyte may contain sulfur (S) and have ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and may include Li—PS-based glass or Li—PS-based glass-ceramics.

[0048] Specifically, the sulfide-based solid electrolyte may include at least one selected from the group consisting of Li6PS5Cl, Li6PS5Br, Li6PS5I, Li2S-P2S5, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2S5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2 and Li2S-GeS2-ZnS, preferably at least one selected from the group consisting of Li6PS5Cl, Li6PS5Br and Li6PS5I. Li6PS5Cl, Li6PS5Br and Li6PS5I may be argyrodite-type solid electrolytes. In addition, sulfide-based solid electrolytes can be doped with trace elements, for example, Li6PS5Cl can be additionally doped with bromine (Br).

[0049] The polymer-based solid electrolyte is a composite of a lithium salt and a polymer resin, that is, a polymer electrolyte material formed by adding a polymer resin to a solvated lithium salt, and can exhibit a thermal conductivity of about 1×10 -7 S / cm or more, preferably about 1×10 -5 S / cm or above ionic conductivity.

[0050] Non-limiting examples of polymer resins may include at least one of the group consisting of polyether polymers, polycarbonate polymers, acrylate polymers, polysiloxane polymers, phosphazene polymers, polyethylene derivatives and alkylene oxide derivatives (e.g., polyethylene oxide), phosphate polymers, poly-stirred lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ion dissociative groups, etc. In addition, the polymer-based solid electrolyte may include, for example, at least one of the following polymer resins: branched copolymers obtained by copolymerizing a polyethylene oxide (PEO) main chain with an amorphous polymer (e.g., PMMA, polycarbonate, polysiloxane (PDMS) and / or phosphazene) as a comonomer, comb polymers, and cross-linked polymer resins.

[0051] In polymer solid electrolytes, lithium salts are + X - The anions of these lithium salts are not particularly limited, but may include F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - or (CF3CF2SO2)2N - .

[0052] The oxide-based solid electrolyte may contain oxygen (O) and have an ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table. For example, it may include a metal selected from the group consisting of LLTO-based compounds, Li6La2CaTa2O 12 、Li6La2ANb2O 12 (where A is Ca or Sr), Li2Nd3TeSbO 12 、Li3BO 2.5 N 0.5 , Li9SiAlO8, LAGP compounds, LATP compounds, Li 1+ x Ti 2-x Al x Si y (PO4) 3-y (where 0≤x≤1 and 0≤y≤1), LiAl x Zr 2-x (PO4)3 (where 0≤x≤1), LiTi x Zr 2-x At least one of the group consisting of (PO4)3 (wherein 0≤x≤1), LISICON compounds, LIPON compounds, perovskite compounds, nasicon compounds and LLZO compounds.

[0053] The solid electrolyte membrane may further include a binder. The binder is not particularly limited as long as it is generally used in the art.

[0054] For example, the adhesive may include, but is not limited to, acrylonitrile butadiene rubber (NBR), styrene butadiene rubber (SBR), butadiene rubber (BR), styrene-butadiene-styrene copolymer (SBS), polybutadiene (PAN), styrene-ethylene / butylene-styrene block copolymer (SEBS), silicone rubber (SR), hydrogenated nitrile rubber (HNBR), poly(ethylene vinyl acetate) (PEVA), poly(methyl methacrylate) (PMMA), polyisobutylene (PIB), polyacrylate, and the like.

[0055] The content of the binder may be 0.5 wt % to 5 wt % based on the total weight of the solid electrolyte membrane. In addition, the total content of the first solid electrolyte and the second solid electrolyte may be 95 wt % to 99.5 wt % based on the total weight of the solid electrolyte membrane. By including the solid electrolyte and the binder as described above, a solid electrolyte membrane for an all-solid-state battery can be prepared, which can be maintained in a film form while minimizing the content of the binder serving as an ion conductive resistor.

[0056] The solid electrolyte membrane for an all-solid-state battery of the present invention can be prepared by dispersing the first solid electrolyte particles and the second solid electrolyte particles in a solvent to prepare a slurry, then applying the slurry to one side of a release film, drying it, and removing the release film. The slurry may further include a binder.

[0057] The first solid electrolyte particles, the second solid electrolyte particles, and the binder are as described above.

[0058] The solvent may be any solvent capable of dispersing the first solid electrolyte particles, the second solid electrolyte particles, and the binder without particular limitation, such as xylene, hexane, benzene, anisole, isobutyl isobutyrate, toluene, and butyl butyrate.

[0059] The ion conductivity of the solid electrolyte membrane for an all-solid-state battery may be 1 mS / cm to 1.6 mS / cm. The ion conductivity may be measured at room temperature (25° C.).

[0060] All-solid-state battery

[0061] The present invention relates to an all-solid-state battery, which comprises a positive electrode, a negative electrode and a solid electrolyte membrane arranged therebetween, wherein the solid electrolyte membrane may be the solid electrolyte membrane of the present invention as described above.

[0062] The all-solid-state battery is a lithium secondary battery in which there is no limitation on the positive electrode or the negative electrode, and it may be a lithium-air battery, a lithium oxide battery, a lithium sulfur battery, or a lithium metal battery.

[0063] The positive electrode may include a positive electrode collector and a positive electrode active material layer applied to one side or both sides of the positive electrode collector.

[0064] The positive electrode current collector is intended to support the positive electrode active material, and is not particularly limited as long as it has good electrical conductivity and is electrochemically stable within the voltage range of the lithium secondary battery. For example, the positive electrode current collector can be any metal selected from the group consisting of copper, aluminum, stainless steel, titanium, silver, palladium, nickel, and alloys thereof, and combinations thereof, wherein stainless steel can be surface treated with carbon, nickel, titanium or silver, wherein aluminum-cadmium alloy is preferably used as an alloy, and wherein calcined carbon, a non-conductive polymer whose surface is treated with a conductive material, or a conductive polymer can also be used.

[0065] The positive electrode current collector may have a microscopic concavoconvex structure formed on its surface to strengthen adhesion with the positive electrode active material, and may use various forms such as films, sheets, foils, meshes, nets, porous bodies, foams, nonwoven bodies, etc.

[0066] The positive electrode active material layer may include a positive electrode active material and optionally a conductive material and a binder.

[0067] The positive electrode active material may vary depending on the type of all-solid-state battery. For example, the positive electrode active material may include, but is not limited to: layered compounds, such as lithium cobalt oxide (LiCoO2), or lithium nickel oxide (LiNiO2), or compounds substituted with more than one transition metal; lithium manganese oxide, such as Li 1+x Mn 2-x O4 (where 0≤x≤0.33), LiMnO3, LiMn2O3 or LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxide, such as LiV3O8, V2O5 or Cu2V2O7; LiNi 1-x M x O2 (wherein M is Co, Mn, Al, Cu, Fe, Mg, B or Ga; and 0.01≤x≤0.3) represented by Ni-type lithium nickel oxide; represented by the formula LiMn 2-x M x A lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is Co, Ni, Fe, Cr, Zn or Ta; and 0.01≤x≤0.1); or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu, Zn); x Mn 2-x Lithium manganese composite oxide with spinel structure represented by O4; LiCoPO4; LiFePO4; elemental sulfur (S8); or sulfur compounds such as Li2S n (where n is 1), organic sulfur compounds or carbon sulfur polymers ((C2S x ) n , wherein x is 2.5 to 50, and n is 2).

[0068] The conductive material is a material that electrically connects the electrolyte and the cathode active material and serves as a path for electrons to migrate from the current collector to the cathode active material, and can be used without limitation as long as it does not cause any chemical changes in the lithium secondary battery and has porosity and conductivity.

[0069] For example, the conductive material can be a porous carbon material, such as carbon black, graphite, graphene, activated carbon or carbon fiber; a metal fiber, such as a metal mesh; a metal powder, such as copper, silver, nickel or aluminum; or an organic conductive material, such as a polyphenylene derivative. These conductive materials can be used alone or in combination.

[0070] Products currently commercially available as conductive materials include acetylene black series (eg, Chevron Chemical Company or Gulf Oil Company), Ketjen Black EC series (Armak Company), Vulcan XC-72 (Cabot Company), and Super P (MMM). Examples include acetylene black, carbon black, and graphite.

[0071] In addition, the positive electrode may further include a binder, which further increases the adhesion between the components constituting the positive electrode and their adhesion to the current collector, and any binder known in the art can be used.

[0072] For example, the binder may be one selected from the group consisting of, or a mixture or copolymer of two or more of the following: fluoroplastic binders, including polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE); rubber-like binders, including styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, and styrene-isoprene rubber; cellulose binders, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyol binders; polyolefin binders, including polyethylene and polypropylene; polyimide binders; polyester binders; and silane binders.

[0073] The negative electrode may include a negative electrode current collector and a negative electrode active material located on the negative electrode current collector. In addition, similar to the positive electrode, the negative electrode may include a conductive material and a binder as needed. In this case, the negative electrode current collector, conductive material, and binder are as described above.

[0074] The negative electrode active material may be any material capable of reversibly inserting or extracting lithium ions (Li + ) and any material capable of reacting with lithium ions to reversibly form a lithium-containing compound.

[0075] For example, the negative electrode active material may include, but is not limited to: one or more carbonaceous materials selected from the group consisting of crystalline artificial graphite, crystalline natural graphite, amorphous hard carbon, low-crystalline soft carbon, carbon black, acetylene black, Ketjen black, super-P, graphene, and fibrous carbon, Si-based materials, Li x Fe2O3 (where 0 ≤ x ≤ 1), Li x WO2 (where 0 ≤ x ≤ 1), and Sn x Me 1-x Me' y O z (where Me is Mn, Fe, Pb, or Ge; Me' is Al, B, P, Si, an element of Group 1, 2, or 3 of the periodic table, or a halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8); lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides, such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5; conductive polymers, such as polyacetylene; Li-Co-Ni-based materials; titanium oxide; or lithium titanium oxide.

[0076] In addition, the negative electrode may include a negative electrode current collector and a coating layer including metal-carbon composite particles on the negative electrode current collector. This may indicate no anode, meaning that the negative electrode does not include any negative electrode active material.

[0077] The negative electrode may allow lithium ions to pass through the coating layer to reach the surface of the negative electrode current collector and be electrodeposited to form a lithium metal layer when the all-solid-state battery is charged.

[0078] The metal-carbon composite particles may have carbon particles and metal particles attached to or coated on each other's surfaces, and may be physically or chemically combined.

[0079] The carbon particles may include natural graphite, artificial graphite, hard carbon, soft carbon, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon nanotubes, fullerenes, carbon fibers, and fluorocarbons.

[0080] The metal particles are lithium-philic metals, such as Ni, Cu, Ag, Au, Pt, Al, Zn or Bi, and may be one or a combination of two or more thereof. By introducing the metals having the above-mentioned lithium-philic properties, it is beneficial to form a stable and uniform lithium layer on the surface of the current collector.

[0081] The negative electrode may be prepared by mixing a binder solution and composite particles to prepare a slurry for coating layer formation, and then applying the slurry to the negative electrode current collector and drying. In this case, the binder may be a conventional binder used in the art.

[0082] The present invention has no particular limitation on the preparation of the all-solid-state battery, and known methods may be used.

[0083] For example, a solid electrolyte membrane is disposed between the positive electrode and the negative electrode, and the battery cell is assembled by compression molding. The assembled battery cell is then installed in an external material and sealed by hot pressing. As the external material, a laminate package of aluminum or stainless steel and a metal container such as a cylindrical or prismatic container can be used.

[0084] In one example, the positive and negative electrodes are prepared by a slurry coating process in which the electrodes are prepared in the form of a slurry composition including corresponding electrode active materials, a solvent, and a binder, coated, and then dried.

[0085] The method of coating the electrode slurry on the current collector may include distributing the electrode slurry on the current collector and uniformly dispersing the electrode slurry using a scraper, die casting, comma coating or screen printing. In addition, the electrode slurry can be formed on a separate substrate and then bonded to the current collector by pressing or laminating. In this case, the final coating thickness can be controlled by adjusting the concentration of the slurry solution or the number of coating layers.

[0086] The drying process is a process of removing solvent and moisture from the slurry to dry the slurry coated on the metal current collector, and the drying process may vary depending on the solvent used. For example, the drying process is carried out in a vacuum oven at 50°C to 200°C. Drying methods include, for example, drying by warm air, hot air or low humidity air, vacuum drying or irradiation with (far) infrared or electromagnetic radiation. The drying time is not particularly limited, but is generally 30 seconds to 24 hours.

[0087] After the drying process, the process may further include a cooling process, wherein the cooling process may be a slow cooling to room temperature to ensure that the recrystallized structure of the binder is well formed.

[0088] In addition, if necessary, in order to increase the capacity density of the electrode and improve the adhesion between the current collector and the active material after the drying process, a rolling process may be performed, in which the electrode is passed between two rollers heated to a high temperature and compressed to a desired thickness. In the present invention, the rolling process is not particularly limited, and any known rolling process may be used. For example, the rolling process may be performed by passing the electrode between rotating rollers or by using a flatbed press.

[0089] The shape of the all-solid-state battery is not particularly limited, and may be cylindrical, stacked, coin-shaped, or the like.

[0090] Example

[0091] Hereinafter, preferred examples of the present invention are described in order to illustrate the present invention, but it is obvious to those skilled in the art that various changes and modifications can be made within the scope and technical concept of the present invention, and these changes and modifications fall within the scope of the appended claims.

[0092] <Preparation of all-solid-state batteries>

[0093] Example 1

[0094] Argentum-type Li6PS5Cl with a Young's modulus of 42 GPa and an average particle size (D50) of 2.5 μm was used as the first solid electrolyte particle. Argentum (Li6PS5Cl) with a Young's modulus of 18 GPa and an average particle size (D50) of 2.5 μm was used as the second solid electrolyte particle. Butadiene rubber was used as a binder.

[0095] The first solid electrolyte particles, the second solid electrolyte particles and the binder were added to a butyl butyrate solvent to prepare a slurry, wherein the weight ratio of the first solid electrolyte particles to the second solid electrolyte particles was 5:5. Furthermore, the weight ratio of the first solid electrolyte particles, the second solid electrolyte particles and the binder was 49:49:2.

[0096] Polyethylene terephthalate was used as a release film, and the slurry was coated on the release film using a bar coater. The release film was then dried at room temperature for 5 hours, and the release film was removed to prepare a solid electrolyte membrane for an all-solid-state battery. The Young's modulus of the solid electrolyte membrane for an all-solid-state battery was 30 GPa.

[0097] The positive electrode active material (NCM811), conductive material (carbon fiber), solid electrolyte (Li6PS5Cl) and binder (polytetrafluoroethylene) were mixed in a weight ratio of 84:0.2:14.8:1, and the mixture was applied to a positive electrode current collector and roll-pressed to prepare a positive electrode.

[0098] A mixture of a negative electrode active material (carbon black) and a binder (polyvinylidene fluoride) was coated with a thickness of 150 μm on SUS having a thickness of 10 μm as a negative electrode current collector, thereby manufacturing a negative electrode.

[0099] The solid electrolyte membrane was disposed between the positive electrode and the negative electrode and a driving pressure of 10 MPa was applied using a jig, thereby preparing an all-solid-state battery.

[0100] Comparative Example 1

[0101] The same process as in Example 1 was performed to prepare an all-solid-state battery, except that argyrodite-type Li6PS5Cl having a Young's modulus of 42 GPa and an average particle size (D50) of 2.5 μm was used as the first solid electrolyte particle, the second solid electrolyte was not used, and the first solid electrolyte particle was used at twice the content of Example 1. The Young's modulus of the solid electrolyte membrane for the all-solid-state battery was 42 GPa.

[0102] Comparative Example 2

[0103] The same process as in Example 1 was performed to prepare an all-solid-state battery, except that argyrodite-type Li6PS5Cl having a Young's modulus of 18 GPa and an average particle size (D50) of 2.5 μm was used as the second solid electrolyte particle, the first solid electrolyte particle was not used, and the second solid electrolyte particle was used at twice the content of Example 1. The Young's modulus of the solid electrolyte membrane for the all-solid-state battery was 18 GPa.

[0104] Comparative Example 3

[0105] The all-solid-state battery was prepared by following the same process as in Example 1, except that the first solid electrolyte particles and the second solid electrolyte particles were mixed at a weight ratio of 2:8.

[0106] Comparative Example 4

[0107] The all-solid-state battery was prepared by following the same process as in Example 1, except that argyrodite-type Li6PS5Cl with an average particle size (D50) of 0.6 μm was used as the second solid electrolyte particle.

[0108] Experimental Example 1. Measurement of Life Characteristics of All-Solid-State Batteries

[0109] The life characteristics of the all-solid-state batteries of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 4 were measured.

[0110] The life characteristics were measured by the capacity retention of 100 charge and discharge cycles of the all-solid-state batteries of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 4. In each cycle, the batteries were charged to 4.25 V at 0.33 C in CCCV mode at a temperature of 60° C. and discharged to 3.0 V at a constant current.

[0111] The results of Example 1, Comparative Example 1 and Comparative Example 2 are Figure 1 Shown in.

[0112] according to Figure 1 As a result, the all-solid-state battery including the solid electrolyte membrane of the present invention of Example 1 has the best life characteristic measurement result.

[0113] Comparative Example 1 contains only argyrodite-type Li6PS5Cl having a Young's modulus of 42 GPa and an average particle size (D50) of 2.5 μm as solid electrolyte particles, and does not contain second solid electrolyte particles. In Comparative Example 1, the interfacial bonding force between the solid electrolyte membrane and the positive electrode and the interfacial bonding force between the solid electrolyte membrane and the negative electrode are very low, resulting in deterioration of the life characteristics of the all-solid-state battery.

[0114] Comparative Example 2 contains only argyrodite (Li6PS5Cl) having a Young's modulus of 18 GPa and an average particle size (D50) of 2.5 μm as solid electrolyte particles, and does not contain the first solid electrolyte particles. Comparative Example 2 shows that the ionic conductivity of the solid electrolyte membrane is low, resulting in an increase in the resistance of the all-solid-state battery and deterioration in the life characteristics of the all-solid-state battery.

[0115] The results of Comparative Example 4 are Figure 2 Shown in.

[0116] In Comparative Example 4, argyrodite-type Li6PS5Cl having an average particle size (D50) of 0.6 μm was used as the second solid electrolyte particle, and since it was difficult to disperse the second solid electrolyte particle during the preparation of the solid electrolyte membrane, an uneven solid electrolyte membrane was prepared. Therefore, the life characteristics of the all-solid-state battery were very poor.

[0117] Experimental Example 2: Measurement of rate characteristics of all-solid-state batteries

[0118] The rate characteristics of the all-solid-state batteries of Example 1, Comparative Example 2, and Comparative Example 3 were measured.

[0119] The rate characteristics were measured by charging from 3.0 V to 4.25 V at 0.1 C and discharging at 0.1, 0.33, 0.5, and 1 C.

[0120] The results of Example 1, Comparative Example 2 and Comparative Example 3 are Figure 3 Shown in.

[0121] according to Figure 3 As a result, the all-solid-state battery (Example 1) including the solid electrolyte membrane of the present invention showed excellent rate characteristics.

[0122] Comparative Example 2 contains only argyrodite-type Li6PS5Cl having a Young's modulus of 18 GPa and an average particle size (D50) of 2.5 μm as solid electrolyte particles, and does not contain the first solid electrolyte particles. In Comparative Example 2, since the ionic conductivity of the solid electrolyte membrane is low, the resistance of the all-solid-state battery increases, resulting in poor rate characteristics of the all-solid-state battery.

[0123] Comparative Example 3 provided a mixture of the first solid electrolyte particles and the second solid electrolyte particles in a weight ratio of 2:8, which showed improved rate characteristics compared to Comparative Example 2, but did not show rate characteristic results as good as Example 1.

[0124] Based on these comparisons, it was found that an all-solid-state battery comprising the following solid electrolyte membrane for an all-solid-state battery has excellent life characteristics and rate characteristics: the solid electrolyte membrane comprises first solid electrolyte particles and second solid electrolyte particles, wherein the Young's modulus of the first solid electrolyte particles is higher than the Young's modulus of the second solid electrolyte particles, wherein the average particle size (D50) of the first solid electrolyte particles and the second solid electrolyte particles is 1 to 5 μm, and wherein the first solid electrolyte particles and the second solid electrolyte particles are mixed in a weight ratio of less than 7:3 to 2:8.

[0125] It was found that this was because the solid electrolyte membrane had an effect of minimizing the resistance at the interface between the positive electrode and the solid electrolyte membrane and the resistance at the interface between the negative electrode and the solid electrolyte membrane.

Claims

1. A solid electrolyte membrane for an all-solid-state battery, comprising: first solid electrolyte particles and second solid electrolyte particles, in, The Young's modulus of the first solid electrolyte particle is higher than that of the second solid electrolyte particle. The average particle size (D50) of the first solid electrolyte particles and the second solid electrolyte particles is 1 μm to 5 μm. The first solid electrolyte particles and the second solid electrolyte particles are mixed in a weight ratio of less than 7:3 to 2:

8.

2. The solid electrolyte membrane according to claim 1, wherein The first solid electrolyte particles have a Young's modulus of 40 GPa to 80 GPa.

3. The solid electrolyte membrane according to claim 1, wherein The second solid electrolyte particles have a Young's modulus of 5 GPa to 30 GPa.

4. The solid electrolyte membrane according to claim 1, wherein The difference between the Young's modulus of the first solid electrolyte particles and the second solid electrolyte particles is 15 GPa to 50 GPa.

5. The solid electrolyte membrane according to claim 1, wherein The particle diameter (D50) of the first solid electrolyte particles and the second solid electrolyte particles is 2 μm to 3 μm.

6. The solid electrolyte membrane according to claim 1, wherein The first solid electrolyte particles and the second solid electrolyte particles are mixed in a weight ratio of 6:4 to 4:

6.

7. The solid electrolyte membrane according to claim 1, wherein The first solid electrolyte particles and the second solid electrolyte particles include at least one selected from the group consisting of a sulfide-based solid electrolyte, a polymer-based solid electrolyte, and an oxide-based solid electrolyte.

8. The solid electrolyte membrane according to claim 7, wherein: The first solid electrolyte particles and the second solid electrolyte particles are sulfide-based solid electrolytes.

9. The solid electrolyte membrane according to claim 1, wherein The solid electrolyte membrane further includes a binder.

10. The solid electrolyte membrane according to claim 9, wherein The binder may be included in an amount of 0.5 wt % to 5 wt % based on the total weight of the solid electrolyte membrane.

11. An all-solid-state battery comprising: a positive electrode, a negative electrode and a solid electrolyte membrane disposed therebetween, in, The solid electrolyte membrane is the solid electrolyte membrane according to claim 1.

12. The all-solid-state battery according to claim 11, wherein: The negative electrode comprises a negative electrode current collector and a negative electrode active material located on the negative electrode current collector; or, The negative electrode includes a negative electrode current collector and a coating layer including metal-carbon composite particles on the negative electrode current collector.

Citation Information

Patent Citations

  • All solid secondary battery and method of manufacturing the same

    KR1020210087919A

  • Apparatus and method for communication

    KR1020230063088A